Legal and Ethical Debate on Escorts on Public Roads: A Comparative Case Study - Sebastian, Muhammad vino; Akmala, Ali Faza; Torin, Muhammad Farrel Arrizky; Soegiarto, Ronald Christyanto (Journal of Law, Politic and Humanities, 2026)
Abstract: This research provides an extensive inquiry into the systemic conflict between judicial mandates and administrative finality within the Indonesian electoral justice system. By focusing on the high-profile disqualification and subsequent legal reinstatement of DPD candidate Irman Gusman, this study dissects the implementation of the principle of legal certainty (asas kepastian hukum) amidst the rigid progression of election stages. Using a normative-juridical framework, the paper evaluates the Jakarta State Administrative Court’s (PTUN Jakarta) findings regarding procedural maladministration and substantive misinterpretations of criminal law by the General Election Commission (KPU). Furthermore, it explores the broader implications of institutional resistance, where the KPU utilized the "non-executable" doctrine to ignore a final and binding court order. The eventual resolution through the Constitutional Court’s (MK) intervention, which ordered a province-wide re-vote, serves as a testament to the high cost of administrative disobedience. This study concludes that the lack of synchronization between judicial timelines and logistical calendars creates a "crisis of certainty" that requires urgent legislative reform to ensure that the rule of law (rechtsstaat) remains the ultimate arbiter of democratic eligibility.